Answer:42
Step-by-step explanation:
Answer:
x<-3
Step-by-step explanation:
x-1+1<-4+1
x<-3
First make x the subject:-
3x = F(x) + 4
x = (F(x) + 4) / 3
f(-1(x) = (x + 4) / 3 answer
Answer:
2 long x tiles and 3 long x tiles are like terms.
Step-by-step explanation:
This is easy to do because you can factor
example
6/2=3 because 6=2*3 so 6/2=3/1 times 2/2 or 3
2x^3+17x^2+23x-42 can be factored out to equal
(x-1)(x+6)(2x+7)
so [(x-1)(x+6)(2x+7)]/(2x+7)=[(x-1)(x+6)] times (2x+7)/(2x+7)=(x-1)(x+6)=x^2+5x-6
the answer is (x-1)(x+6) or x^2+5x-6